The diversity of diurnal bird's species in Sungai Chongkak Recreational Forest Selangor - Mudani, Amin Bakri; Yusof, Ebil; Hussin, Mohamed Zakaria; Mohamad Kasim, Mohamad Roslan (Zes Rokman Resources, 2016)
Malaysia has many species of flora and fauna. This is because Malaysia is among 17 mega biodiversity country in the world. Malaysia has many recreational forest areas. The values of the recreational forest area are normally dependent on the species of flora and fauna that lives at the area. Sungai Chongkak Recreational Forest (SCRF) Selangor is among popular recreational forest in Selangor state but no research on diurnal bird’s species has been conducted at the area. Diurnal bird’s species are among the important species that help to maintain the forest growing and healthy forest. Other than that, the identification of diurnal bird’s species that lives at SCRF can help SCRF to promote bird watching activities to the visitor. The study about the diversity of diurnal bird’s species in Sungai Chongkak Recreational Forest Selangor has been conducted. The results of the study indicate that SCRF Selangor lives with many species of diurnal birds. There are 41 species of diurnal birds from 20 families has been observed and the number of observed birds is 524 observed birds.